Ð’Ð¿Ð»Ð¸Ð² Ð»Ñ–Ð¾Ñ„Ñ–Ð»Ñ–Ð·Ð¾Ð²Ð°Ð½Ð¾Ð³Ð¾ Ð»Ð°ÐºÑ‚Ð¾Ñ„ÐµÑ€Ð¸Ð½Ñƒ Ð½Ð° ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€Ñƒ ÐºÐ»Ñ–Ñ‚Ð¸Ð½ Arn8 Ð² Ð½Ð¾Ñ€Ð¼Ð°Ð»ÑŒÐ½Ð¸Ñ… ÑƒÐ¼Ð¾Ð²Ð°Ñ… Ñ‚Ð° Ð¿Ñ–ÑÐ»Ñ ÑƒÐ»ÑŒÑ‚Ñ€Ð°Ñ„Ñ–Ð¾Ð»ÐµÑ‚Ð¾Ð²Ð¾Ð³Ð¾ Ð¾Ð¿Ñ€Ð¾Ð¼Ñ–Ð½ÑŽÐ²Ð°Ð½Ð½Ñ - Galchenko, K. S. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2002)
The effect of lactoferrin (LF) on Arn8 cell culture in normal conditions and after ultraviolet (UV) irradiation has been studied. It was defined that LF did not initiate the progression of cells with damaged DNA into proliferation cycle. The effect of LF from bovine colostrum as well as human LF on Arn8 cells has been also studied. It was shown that incubation of cells with LF from bovine colostrum leads to much greater loss of cell viability than in cells incubated with human LF.